Addressing housing needs of the displaced people promoting resilient and sustainable communities. Issue 3 (30th March 2022) - Jayakody, Chathuranganee; Malalgoda, Chamindi Ishara; Amaratunga, Dilanthi; Haigh, Richard; Liyanage, Champika; Hamza, Mo; Witt, Emlyn; Fernando, Nishara
Abstract : Purpose: Addressing the housing needs of the displaced communities is an essential part of a recovery programme that has distinct links to livelihoods, health, education, security and social and family stability. The housing factor acts as a social centre for family and friends, a source of pride and cultural identity and a resource that commands both political and economic importance. Therefore, addressing the housing needs of the displaced communities should be seen as a mode to promote resilience and sustainable communities. Instead, the consideration of housing needs merely as a physical need results in many issues to the communities, including no access to livelihood, poor living condition, health problems, lack of financial independence, lack of social satisfaction and social cohesion, and sometimes even recreates and worsens the existing vulnerabilities of displaced communities. Within this context, the purpose of this paper is to investigate the factors to consider when addressing the housing needs of the displaced communities, promoting resilience and sustainable communities. Design/methodology/approach: The research team of the project titled REbuildinG AfteR Displacement (REGARD) conducted 47 in-depth interviews in four partner countries (the UK, Sweden, Estonia and Sri Lanka) with officials, community representatives, social support networks, agency networks, etc. Apart from that, focus group discussions were conducted with the community members in Sri Lanka covering both conflict-induced and disaster-induced displacement. Findings: The findings of this paper revealed that the housing factor has a significant role in rebuilding communities and determining the long-term satisfaction of displaced communities. Further, the results present eight essential factors to consider when addressing the housing needs of the displaced communities, promoting resilient and sustainable communities. Practical implications: The findings are helpful for future planners, urban designers, architects and policymakers who work in the resettlement field. Planners, urban designers and architects can use these identified factors to cross-check their resettlement planning and designing strategies in addressing the housing needs of the displaced communities. Further, policymakers can mainstream these identified factors into the resettlement housing-related policies and regulations. Originality/value: Addressing the housing needs of the displaced communities is an essential part of a recovery programme that has distinct links to livelihoods, health, education, security and social and family stability. The housing factor acts as a social centre for family and friends, a source of pride and cultural identity and a resource that commands both political and economic importance. Therefore, addressing the housing needs of the displaced communities should be seen as a mode to promote resilience and sustainable communities. Instead, the consideration of housing needs merely as a physical need results in many issues to the communities, including no access to livelihood, poor living condition, health problems, lack of financial independence, lack of social satisfaction and social cohesion, and sometimes even recreates and worsens the existing vulnerabilities of displaced communities. Within this context, this paper investigates the factors to consider when addressing the housing needs of the displaced communities, promoting resilience and sustainable communities.